The formation of a barrier-free environment in the historical apartment buildings in Lviv - Pekarchuk, Оksana (Lviv Polytechnic Publishing House, 2015)
The features of adaptation historical apartment buildings in Lviv to the needs of group of people with limited mobility (LMG) are discussed in the article and presented draft proposals for its implementation.
Keywords: historical apartment buildings; group of people with limited mobility; barrier-free environment